2009
DOI: 10.1161/circheartfailure.108.802298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiac Myosin Isoform Variation on Myofilament Function and Crossbridge Kinetics in Transgenic Rabbits

Abstract: Background-The left ventricles of both rabbits and humans express predominantly ␤-myosin heavy chain (MHC).Transgenic (TG) rabbits expressing 40% ␣-MHC are protected against tachycardia-induced cardiomyopathy, but the normal amount of ␣-MHC expressed in humans is only 5% to 7% and its functional importance is questionable. This study was undertaken to identify a myofilament-based mechanism underlying tachycardia-induced cardiomyopathy protection and to extrapolate the impact of MHC isoform variation on myofila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…This result may not be surprising considering that previous studies have shown that myosin S1 and singleheaded myosin have different properties than even heavy meromyosin (55). In agreement with our results, the apparent rates of ADP dissociation measured from the rabbit, rat, and human myofibrils were similar to the calculated rates of ADP dissociation measured by the laser trap assay (rabbit and rat) (41,44) and from the sinusoidal length perturbation analysis of crossbridge detachment (human, rabbit, and rat) (52)(53)(54).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result may not be surprising considering that previous studies have shown that myosin S1 and singleheaded myosin have different properties than even heavy meromyosin (55). In agreement with our results, the apparent rates of ADP dissociation measured from the rabbit, rat, and human myofibrils were similar to the calculated rates of ADP dissociation measured by the laser trap assay (rabbit and rat) (41,44) and from the sinusoidal length perturbation analysis of crossbridge detachment (human, rabbit, and rat) (52)(53)(54).…”
Section: Discussionsupporting
confidence: 92%
“…Previously, the rates of ADP dissociation from different cardiac myosins were inferred from the study of unregulated actomyosin in solution (20), laser trap experiments (44), and sinusoidal analysis on skinned cardiac muscle (52)(53)(54). The apparent rate of ADP dissociation measured by our fluorescent TnC is nearly one order of magnitude slower than that measured from actomyosin in solution for the different fast and slow myosins (20).…”
Section: Discussionmentioning
confidence: 86%
“…Increasing ␣-MyHC by just 12% is sufficient to increase single cardiac myocyte power output by ϳ50% (43). In transgenic rabbits that express 15% ␣-MyHC, ventricular papillary muscles reportedly generate 20% greater peak power output than nontransgenic samples expressing 100% ␤-MyHC (49). Finally, mathematical modeling predicts that just 10% ␣-MyHC (90% ␤-MyHC) can enhance myocardial twitch kinetics and amplitude independent of the calcium transient (15).…”
Section: How Much ␣-Myhc Is Required To Augment Cardiac Contractility?mentioning
confidence: 98%
“…3,4 The same directional shift occurs in humans; because human myocardium normally consists of ≈90% β-MyHC, its magnitude is small and functional consequences seem modest. 4,5 Ventricular expression of the atrial isoform of the myosin essential light chain is elevated in DCM and would be expected to improve contractile performance. 6 Titin, the giant protein that accounts for cardiomyocyte passive stiffness, undergoes a shift to its more compliant N2BA isoform in human DCM.…”
Section: Editorial Myofilament Proteins In Genetic and Acquired Heartmentioning
confidence: 99%